Percepción de padres sobre la atención Odontológica a sus hijos en una universidad pública de Paraguay - Gamarra Insfrán, José Miguel (2024)
Objective: Determine the perception of parents about dentist attention to their child´s at a public university in Paraguay. Methodology: An observational, descriptive, cross-sectional study was designed. Through non-probabilistic convenience sampling, 80 adult parents and/or direct caregivers of children who came for dental care were part of the study. A self-completed questionnaire was applied. The instrument has 17items to determine the satisfaction of those responsible for the dental care provided to children, considering three dimensions. The response options are Likert type, with five possible options. To determine the quality of the care provided, a scale was established giving a numerical value to each selected response regarding the level of satisfaction, and all responses were added individually. Results: In the three dimensions analyzed, a greater number of positive responses were observed for the different items consulted, with most cases being classified as “very satisfied.” Regarding quality, only 3.7% of those surveyed perceive that the quality of care is low, 12.5% average quality and 83.7% high quality. Conclusion: According to the perception of parents and/or guardians, the quality of care offered in the chair of comprehensive dentistry for children is high. This is coincides to the positive responses that were obtained in the different items of the three dimensions.